Heart rate response towards fear-eliciting stimuli in horses - Hedman, Jenny (SLU/Dept. of Animal Environment and Health (until 231231), 2003)
Finding the right horse for each rider is a difficult task as it is just as important that the temperament of the horse fits the rider as it is that the horse is of the right size. Even though it is a commonly experienced problem, no objective method of easily measuring the horse's temperament has yet been developed. If it is possible to test horses and get an objective measure of how reactive (emotional) they are, it could be a big help in finding the right horse for each rider. It would be desirable to have a way of testing the horse's reaction in an unfamiliar (and potentially frightening) situation. In practice this test should be just as easy as it is getting a judgement of its conformation and gaits.